2009
DOI: 10.1103/physrevd.79.064031
|View full text |Cite
|
Sign up to set email alerts
|

Universal properties of the near-horizon optical geometry

Abstract: We make use of the fact that the optical geometry near a static non-degenerate Killing horizon is asymptotically hyperbolic to investigate universal features of black hole physics. We show how the Gauss-Bonnet theorem allows certain lensing scenarios to be ruled in or out. We find rates for the loss of scalar, vector and fermionic `hair' as objects fall quasi- statically towards the horizon. In the process we find the Lienard-Wiechert potential for hyperbolic space and calculate the force between electrons med… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 26 publications
0
51
0
Order By: Relevance
“…In particular in [8] the Gaussian curvature of the Schwarzschild optical metric restricted to the equstorial plane was shown to be everywhere negative and to approach a constant value near the horizon r = 2M. In [9] this behaviour was found to be universal for the near horizons of non-extreme static black holes. One purpose of the present paper is to extend this work to the case of massive particles.…”
Section: Introductionmentioning
confidence: 93%
“…In particular in [8] the Gaussian curvature of the Schwarzschild optical metric restricted to the equstorial plane was shown to be everywhere negative and to approach a constant value near the horizon r = 2M. In [9] this behaviour was found to be universal for the near horizons of non-extreme static black holes. One purpose of the present paper is to extend this work to the case of massive particles.…”
Section: Introductionmentioning
confidence: 93%
“…The conformal Riemannian metric on M , g 0 /Λ is called optical metric. It plays a fundamental role in the study of light rays of I × Λ M because its pregeodesics are the projections on M of the light rays in (I × M, g) (see [3], [21], [37]). Moreover, many of the causal properties of the spacetime I × Λ M are encoded in the geometry of the conformal manifold (M, g 0 /Λ).…”
Section: Standard Static Finsler Spacetimesmentioning
confidence: 99%
“…One of the early workers on this topic was Pin [13] who considered many body systems and in particular showed that the Gaussian curvature of the Jacobi metric has a sign opposite to the particle energy E (non-relativistic, without the rest energy). In later times Gibbons et al [14][15][16][17] have considered the optical metric in various physical situations which is a closely related concept for massless particles. Discussions of the Jacobi-metric approach in a modern perspective can be found in [18].…”
Section: Maupertuis Principle and Jacobi Metricmentioning
confidence: 99%